Peran Teknologi Informasi Dalam Mendukung Komunikasi Politik Melalui Media Digital Dalam Industri Musik Dangdut: The Role of Information Technology in Supporting Political Communication Through Digital Media in the Dangdut Music Industry ​ - Hariyanto, Bambang; Anom, Erman; Iswadi (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2024)
The aim of this research is to find out the other side of communication media used in a political context, especially in the aspect of digital technology media. Specifically, this research examines the function of dangdut music and digital technology media as communication tools in political spaces that are common in Indonesia. The method used in this research is a qualitative research method, with the type of research being a case study. Based on research conducted, it is known that the use of dangdut music in political communication has had a positive impact on party electability. Dangdut music with its broad appeal, its ability to build emotional bonds, and its potential to create a positive and viral atmosphere on various digital platforms in political campaigns has helped political parties or candidates to win the hearts of voters. However, the use of dangdut music is only one element of an effective political communication strategy. A strong political message, convincing leadership, and a well-organized campaign plan are also important factors in achieving high electability.